Pengelolaan Cfa pada Instrumen Skala Body Appreciation Scale (Bas-2) Menggunakan Software Lisrel - Sholikhah, Nikmatus; Nirwana, Nila Turkhudus; Sakha, Nisrina Nabila; Nurmalitasari, Femmi (Universitas Negeri Malang, 2024)
Body appreciation is a concept that refers to the appreciation or positive regard an individual has for their own body. Understanding body perception plays a crucial role as it can shape an individual’s self-concept. Individuals with good body appreciation are often linked to better well-being. Developing instruments related to body appreciation in a cultural context is essential, as it allows for measuring body appreciation within a specific culture. The aim of this study is to examine the construct validity of the Body Appreciation Scale (BAS-2) instrument. This research is a quantitative study using the Confirmatory Factor Analysis (CFA) measurement model. Participants in this study were college students aged 18–25 years from across Indonesia. The initial CFA results indicated that some models were not a good fit, prompting modifications to achieve a model that meets the fit criteria. After achieving an overall data fit, further validity and reliability tests showed that the convergent validity was not met. Thus, the BAS-2 instrument in this study needs to be retested in future research. AbstrakBody appreciation merupakan konsep yang merujuk pada penghargaan atau apresiasi yang seseorang miliki terhadap tubuhnya sendiri. Pemahaman terhadap persepsi tubuh memberi peranan penting karena hal ini dapat membentuk konsep diri bagi individu. Individu dengan body appreciation yang baik cenderung berhubungan dengan well-being. Pengembangan instrumen terkait body appreciation dalam konteks budaya diperlukan sebab hal ini dapat menjadi upaya pengukuran body appreciation dalam suatu budaya. Tujuan dari penelitian ini adalah untuk menguji validitas konstruk dari instrumen body appreciation scale (BAS-2). Penelitian ini merupakan jenis penelitian kuantitatif dengan model pengukuran Confirmatory Factor Analysis (CFA). Partisipan pada penelitian ini merupakan mahasiswa berusia 18 – 25 tahun di seluruh Indonesia. Hasil CFA awal yang terdapat beberapa model yang tidak fit, lalu dilakukan modifikasi agar mendapatkan hasil yang sesuai dengan kriteria sehingga mendapatkan hasil keseluruhan data fit. Pada pengelolaan hasil fit setelah di uji validitas dan reliabilitas ternyata pada validitas konvergennya tidak terpenuhi. Sehingga instrument BAS-2 pada penelitian ini perlu diuji kembali dengan penelitian selanjutnya.